Waste to Wealth or Windfarm Facility Development in Scotland: Legal, Technical and Socio Economic Issues Involved In Choosing Either - Emetumah, Faisal. C; Duru, Patricia. N (Advances in Social Sciences Research Journal, 2015)
The study looked at the technical, legal and socio economic issues involved in land use planning for choosing a viable renewable energy investment (waste to energy or wind farm facility) as well as public opinion issues with respect to sustainable development. The study tried to evaluate and analyse the key technical, legal and socio economic aspects a landowner will have to deal with in order to set up a functional ‘waste to energy plant’ with respect to the proximity to a residential area. Alternately the paper discussed all the relevant aspects and impacts as regards legal, technical and socio economic conditions a landowner will have, on setting up a windfarm with respect to the possibility of scenery destruction and other issues that the populace will likely find loathsome. Identifying those key issues that opponents and proponents of both projects may have will provide the landowner with the best way to decide the option to choose. Conclusively, the study opined that no matter the choice made, it is important that all the relevant laws, regulations, acts and guidelines provided by the authorities and the opinion of the local population are respected so that while renewable energy is produced, sustainability is maintained.